ВПЛИВ ДИСКРЕТНОГО ХАРАКТЕРУ СИГНАЛУ ШВИДКОСТІ НА ПРОЦЕСИ КЕРУВАННЯ МОМЕНТОМ ВЕКТОРНО-КЕРОВАНОГО АСИНХРОННОГО ДВИГУНА - Ковбаса, С.М.; Красношапка, Н.Д.; Коломійчук, Є.В.; Холоша, А.О.; Делейко , Б.С. (Інститут електродинаміки Національної академії наук України, 2024)
The paper presents the investigation of the impact of the discrete character of the measured by incremental encoder speed signal on the induction motor torque vector control in traction electrical drive. The study is based on mathematical simulations for a direct vector flux-torque control system which provides direct asymptotic field-orientation, asymptotic flux-torque trajectory tracking, and asymptotic decoupling of the torque and flux subsystems. The parameters of the induction motor and encoder used in the study correlate with used in the real traction electromechanical systems of trolleybuses. It is shown that introduction of first order filter in the speed measurement channel reduces the induction motor’s current and torque spikes, but leads to an error in torque control and degradation of the rotor flux field-orientation conditions. Combined utilization of filtered and unfiltered speed signal is proposed in order to avoid this disadvantage.